Isothermal melt crystallization kinetics of poly (L-lactic acid) - Urbanovici, E.; Schneider, H.A.; Brizzolara, D.; Cantow, H.J.
A DSC study was carried out of the isothermal melt crystallization kinetics of poly(L-lactic acid), PLLA, at 110, 115,120, 125 and 130~ The experimental data were evaluated within the framework of the well-known Avrami kinetic model and an extended model involving an additional third kinetic parameter [8]. In order to perform the necessary numerical calculations, a number of functions built into the Mathematiea software system were used. The results showed that the isothermal melt crystallization kinetics of PLLA can be described adequately by both these kinetic models. It should also be stressed that the kinetic model of Urbanovici and Segal offers a better description of the experimental melt crystallization data of PLLA than the classical Avrami model.
Keywords: DSC; ISOTHERMAL MELT CRYSTALLIZATION; KINETIC PARAMETERS; MATHEMATICA; NEW KINETIC MODEL; POLY(L-LACTIE ACID)